2018
DOI: 10.18632/oncotarget.25109
|View full text |Cite
|
Sign up to set email alerts
|

Signature program: a platform of basket trials

Abstract: Investigating targeted therapies can be challenging due to diverse tumor mutations and slow patient accrual for clinical studies. The Signature Program is a series of 8 phase 2, agent-specific basket protocols using a rapid study start-up approach involving no predetermined study sites. Each protocol evaluated 1 agent (buparlisib, dovitinib, binimetinib, encorafenib, sonidegib, BGJ398, ceritinib, or ribociclib) in patients with solid or hematologic malignancies and an actionable mutation. The primary endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Frequent genetic alterations were observed in PIK3CA, RAS, p16 , and PTEN . Overall, 30 partial or complete responses were observed with 6 of the compounds studied, in 16 tumor types [23] . The authors concluded that the Program was a successful approach, because it led to rapid signal finding, reduced patient exposure to toxicity, and substantially shortened trial start-up times .…”
Section: Precision Medicine Clinical Trials: a New Paradigm For Reseamentioning
confidence: 99%
“…Frequent genetic alterations were observed in PIK3CA, RAS, p16 , and PTEN . Overall, 30 partial or complete responses were observed with 6 of the compounds studied, in 16 tumor types [23] . The authors concluded that the Program was a successful approach, because it led to rapid signal finding, reduced patient exposure to toxicity, and substantially shortened trial start-up times .…”
Section: Precision Medicine Clinical Trials: a New Paradigm For Reseamentioning
confidence: 99%
“…While basket trial definitions (n = 35) [[1], [2], [3], [4], [5],11,13,15,18,[23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48]] were consistent on some aspects, such as that basket trials study multiple disease types (n = 34), other features such as the number of interventions to be studied were inconsistent. Approximately half of the reviewed publications (n = 18) [1,2,4,5,11,13,15,25,30,31,33,35,38,39,41,42,45,49] specified that basket trials are designed to evaluate a single intervention, while around a third (n = 10) [3,18,23,[26], [27], [28], [29],36,40,43] stated that they can evaluate multiple interventions. The remaining definitions (n = 7) specified both [37,44,47] or neither [32,34,46,48].…”
Section: Resultsmentioning
confidence: 99%
“…Since basket trials are considered an exploratory approach for signal finding on treatment effect across subpopulations, 12,32 prior information on the heterogeneity and homogeneity of treatment efficacy would be generally limited during trial planning. The proposed method does not require specification of prior information on the heterogeneity and homogeneity of treatment efficacy; however, it requires only two probabilities (eg, π 1 and π 2 ) corresponding to null and alternative models of the true response rates before beginning the trials.…”
Section: Discussionmentioning
confidence: 99%